Credibility Review of the Malaysian States E-government Web Sites - Syahrul Nizam, Bin Junaini; Jonathan, Sidi (National Institute of Public Administration, 2009)
The migration from paper-based services to electronic version has developed the potential of e-government applications enormously. However, designing a credible government web site is not a simple task. This paper discusses the importance of credibility for the Malaysian states government web sites. Top web credibility factors are listed. Reviews on five state government websites are also presented. Assessment of the credibility issues were done on five state government sites, which are Sarawak, Selangor, Johor, Melaka and Kedah Government web site. We found that there are still room for improvement for the sites in terms of credibility and site appearance.